Learning the Real Estate Market Resilience: The Effectiveness of Internet Platforms in Marketing Strategy - Siti Munirah, A G; Ezdihar, H (International Journal of Sustainable Construction Engineering and Technology, 2022)
The era of unprecedented pandemic coronavirus disease (COVID-19) had affected many sectors especially tourism, aviation and sharing accommodation industry, which includes the hotel industry or peer-to-peer accommodation industry. The pandemic situation has also reflected the real estate market as a whole, thus requiring real estate agents to be more creative in marketing strategy from the way they reach imminent clients. Digital trend technology, the Internet and social media appear to have a huge impact on business and have created new marketing chances. Due to that, this research aims to study the effectiveness of Internet platforms by investigating the contents’ ranking of the platforms for marketing strategy by real estate agents. Quantitative analysis was adopted using Relative Importance Index analysis. This study can benefit the body of knowledge and the real estate industry in terms of marketing strategy. This research displayed Facebook as the main platform where businesses conduct their marketing strategy for sales or promoting the property. Furthermore, to lead to sales, estate agents need to post important component on social media and post it regularly to achieve engagement and maximise profit.